Intersection Between Administrative Freies Ermessen and Maladministration in Strategic Nickel Industrial Area Development in Morowali - Tegar Raffi Putra Jumantoro; Muhammad Fadirah Fauzi (Journal of Ius Comparatum Law Studies, 2025)
The development of the nickel industrial zone in Morowali Regency reflects a critical intersection between administrative discretion (freies Ermessen) and the growing risks of maladministration. While the project, primarily through the Indonesia Morowali Industrial Park (IMIP), contributes significantly to national economic growth and global energy transition, its implementation often circumvents legal and ethical governance frameworks. This study employs a normative juridical method with statutory, conceptual, and case approaches to examine the legal boundaries of administrative discretion within strategic national projects. Findings reveal that discretion has been exploited to accelerate permits, land acquisition, and fiscal incentives without sufficient public participation, transparency, or legal compliance. Such practices have led to environmental degradation, agrarian conflicts, and diminished public trust in government institutions. Key indicators of maladministration include abuse of authority, discriminatory policies favoring large corporations, procedural violations, and the absence of effective oversight mechanisms. The research underlines that discretion, when detached from its foundational legal and moral principles, transforms into a tool of unchecked bureaucratic power, undermining good governance and democratic values. It argues for stricter regulatory oversight, clearer discretionary boundaries, and participatory frameworks to prevent misuse in future development agendas. Ultimately, the paper contributes to advancing administrative law discourse by emphasizing the urgent need for institutional reforms to align discretionary practices with the principles of accountability, legality, and public interest in state administration.